One exactly solvable random spin-1/2 XY chain - Derzhko, O. V.; Verkholyak, T. M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
Considering one-dimensional spin-1/2 isotropic XY model with Dzyaloshinskii-Moriya interaction in random Lorentzian transverse field we have calculated exactly thermodynamic quantities of the model. We used the derived average single-particle density of states to examine the validity of coherent potential approximation.